Implementation of Carpool in New House Construction A study questioning the parking ratio regulation in Gothenburg - STRÖMBERG, EMMA (My University, 2016)
Gothenburg city is today working with the challenge to develop a sustainable city and transportation system, where space and resources are used in an optimal way. This raises the discussion of new ways of designing the urban structure. A sustainable city needs to reduce car usage and integration of sustainable mobility solutions is needed already in the planning phase of new dwellings. The aim of this study has therefore been to investigate carpool as a mobility solution in new house construction. The process has included literature research, interviews, calculation comparison and execution of a survey. During the research, it was found that implementation of carpool in new house construction, in the central part of Gothenburg, is beneficial since it contributes to the sustainable development. But it is not easy to implement because the parking ratio regulation requires a special assessment and there is no guarantee this will be approved. Also, it was discovered that the behavioural aspect plays an important role where circumstances in life and the car’s anchoring in the society makes it more complex. Thereby affecting the intrinsic value and in turn the choice of owning a car versus using a carpool. In addition, the result has contributed with stronger reasons to make the actual cost of parking places visible for those who demand a parking place because this might eliminate the subsidizing and the manipulated parking demand. The study concludes there are problems with the parking ratio regulation regarding flexibility, economical rationality and estimation of the parking demand. The recommendation is to apply flexible parking ratios based on a will-controlled approach. In addition, economic rationality and behaviour changes should be taken into consideration in the regulation. Further studies are requested to investigate how to formulate a new regulation in order to work well. An analysis how these kinds of changes would affect people’s travel behaviour and the parking demand is recommended to be done. The contribution has been to rethink the designing of new dwellings and understand that cooperation and communication among different actors is important in order to create updated and well-functioning regulations. Hopefully this can create a debate about how create incentives in regulations to strive for a sustainable development in the built environment.
Keywords: Samhällsbyggnadsteknik; Civil Engineering